Impact of Remittances on Natural Rate of Dollarization-Trends in Caucasus and Central Asia - Gondo, Rocio; Aidarova, Altynai; Singh, Manmohan (Washington, D.C. : International Monetary Fund, 2020)
This paper discusses migration and remittances trends, and calculates the natural (or benchmark) level of dollarization in Caucasus, Central Asia and others in the region. This natural level of dollarization is conceptually linked to the currency allocation in a portfolio of deposits to maximize welfare, in line with Ize and Levy Yeyati (2003). The fall in remittances due to the economic slowdown since the spread of COVID-19 affects the macroeconomic fundamentals that determine demand for foreign currency deposits. We calculate the natural dollarization level by integrating structural macroeconomic characteristics. We show that despite the reduction in deposit dollarization, there is still a gap with respect to the natural level of dollarization, especially in a scenario of (persistent) lower remittance inflows.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet